A novel stable nitritation process: Treating sludge by alternating free nitrous acid/heat shock. (March 2022) - Liu, Chengju; Wang, Yanyan; Chen, Guanghui; Yu, Deshuang; Zhang, Xincheng; Wang, Xueping; Tang, Zhihao; Xu, Ao
Graphical abstract: Highlights: Alternating FNA/heat shock treatment was used to keep stable nitrite accumulation. Nitrite accumulation ratio (NAR) was stable above 90% during the long-term study. The linear regression method was used to determine nitritation parameters. NOB were effectively inhibited and AOB abundance was maximized. Abstract: The feasibility of stable nitritation of sludge alternately treated by free nitrous acid (FNA) and heat shock in a sequencing batch reactor (SBR) was investigated in this study. The linear regression method was used to determine the optimal treatment conditions. Results revealed that an FNA concentration of 2.20 mg HNO2 -N/L, exposure time of 24 h, and treatment ratio of 20% could inhibit nitrite oxidizing bacteria (NOB) activity to the greatest extent while maintaining the maximum ammonium oxidizing bacteria (AOB) activity; after heat shock at 60 °C for 20 min, NOB were inhibited while AOB still had certain activity. In the long-term continuous-flow experiment, the single FNA or heat shock treatments easily allowed adapt NOB to affect the stability of nitritation. The alternating FNA/heat shock treatment can achieve long-term stability of nitritation. Microbial community analysis revealed that the alternating FNA/heat shock treatment could inhibit NOB while maintaining high AOB abundance.